The effect of self-esteem on vocational high school students' mathematics achievement - Anna Mulyana; Arina Silviana; Arsyil Waritsman (Balai Diklat Keagamaan Ambon, 2025)
This study investigates the effect of self-esteem on mathematics achievement among vocational high school (SMK) students. Mathematics is often perceived as a difficult subject that triggers learning anxiety, especially for vocational students who are required to master numerical skills as part of their competencies. The study was conducted at SMK Negeri 1 Tolitoli using a quantitative approach. Data were collected through a self-esteem questionnaire and documentation of mathematics achievement scores, and analysed using simple regression analysis. The findings reveal that self-esteem has a positive and significant effect on students' mathematics achievement. Higher levels of self-esteem are associated with better academic performance, particularly in mathematics. Theoretically, the study contributes to educational psychology literature by reaffirming the role of self-esteem in the vocational education context. Practically, the findings provide a basis for teachers, counsellors, and policymakers in developing learning strategies and counselling programs that foster students' self-esteem. Future research is recommended to include additional variables, such as motivation, learning anxiety, and social support, to achieve a more comprehensive understanding of the topic.